ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN KOPERASI PADA PERIODE 2016-2020 (STUDY PERBANDINGAN KOPERASI KARYA BERSAMA dan MAJU BERSAMA PANGKALAN KURAS PELALAWAN) - Wahyudi, Wisnu Dicky; ', Ruzikna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to analyze financial ratios to measure financial performance of Karya Bersama cooperatives and Maju Bersama Cooperative Pangkalan Kuras Pelalawan. The research instrument used is quantitative descriptive research such as interviews, documentation and theoretical studies. The results of the research showed that the financial performance of Karya bersama cooperative was in good condition in terms of financial ratios and received a fairly good assessment, while Maju Bersama cooperative received a less good assessment so that Maju Bersama cooperative had to improve the financial performance of the cooperative by developing the business it owned. Keywords: Financial Ratios, Financial Performance, Cooperatives